Late proliferating and inflammatory effects on murine microvascular heart and lung endothelial cells after irradiation. Issue 2 (November 2015) - Sievert, Wolfgang; Trott, Klaus-Rüdiger; Azimzadeh, Omid; Tapio, Soile; Zitzelsberger, Horst; Multhoff, Gabriele
Abstract: Background and purpose: Radiotherapy of thoracic tumors increases the risk to develop cardiac diseases at later time-points. We compared time kinetics of radiation-induced changes of surface markers related to proliferation, progenitor cell development and inflammation in lung and heart microvascular endothelial cells (ECs). Material and methods: Mice received local thorax irradiation with a single dose of 0, 2 or 8 Gy. Following magnetic bead separation and biotin-streptavidin competition, cell surface markers of isolated ECs from the lung and heart were analyzed 5, 10, 15 and 20 weeks after irradiation by flow cytometry. Results: Irradiation with 8 Gy resulted in a temporary and differential up-regulation of proliferation markers (HCAM, Integrin β-3, Endoglin, VE-cadherin, VEGFR-2) on ECs. Mucosialin a progenitor marker increased in lung ECs 15–20 weeks and inflammatory markers (PECAM-1, ICAM-1, ICAM-2, VCAM-1) started to increase 10 weeks after thorax irradiation with 8 Gy. Interestingly, ICAM-1 and VCAM-1 remained up-regulated 20 weeks after irradiation in heart and lung ECs. Conclusions: The persistently elevated expression density of ICAM-1 and VCAM-1 on ECs may suggest that an irradiation at 8 Gy induces late inflammatory responses in heart and lung ECs.